2020
DOI: 10.1038/s41598-020-72787-w
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrosive non-crystalline coating prepared by plasma electrolytic oxidation for ship low carbon steel pipes

Abstract: A corrosion-resistant non-crystalline coating was fabricated by plasma electrolytic oxidation (PEO) on Q235 low carbon steel for ship pipes. The distribution and composition of chemical elements and phases of PEO coatings were analyzed by an orthogonal experiment, and the formation mechanism of PEO coatings was discussed. The corrosion current densities and corrosion potentials were measured. The results indicated that the formation of a transition layer mainly containing Fe3O4 was crucial for achieving an exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Q235 low carbon steel is widely used in petroleum production, [1] chemical processing, [2] shipbuilding industry, [3] and other industries because of its low cost, [4] good mechanical properties, [5] and high strength. [6] However, the corrosion resistance of Q235 low carbon steel is poor, [7] resulting in economic losses and environmental damage. Epoxy resin is widely used in the corrosion protection of low carbon steel.…”
Section: Introductionmentioning
confidence: 99%
“…Q235 low carbon steel is widely used in petroleum production, [1] chemical processing, [2] shipbuilding industry, [3] and other industries because of its low cost, [4] good mechanical properties, [5] and high strength. [6] However, the corrosion resistance of Q235 low carbon steel is poor, [7] resulting in economic losses and environmental damage. Epoxy resin is widely used in the corrosion protection of low carbon steel.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon steel has several attractive properties, such as high strength, good malleability, ductility, plasticity, easy forging, welding, and cutting, all combined with a relatively low cost [1][2][3] . Such characteristics make this metal proper to be applied in several sectors, such as in the cutting tool industry, in the manufacture of plates, sheets, bars, and tubes of the metallurgical industry, and civil construction [3][4][5] . However, despite its widespread use, carbon steel is not a perfect material, as it has low resistance to wear and corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al 3 , deposited a non-crystalline coating resistant to corrosion using PEO in an electrolyte composed of sodium silicate, sodium carbonate, and distilled water on low carbon steel Q235. The results of potentiodynamic polarization tests in NaCl 3.5% w/w demonstrated that there was a 78% reduction in the value of corrosion current density, I corr , in coated steel compared to uncoated steel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…bioactive glass for better osseointegration [12] or basalt mineral fibers for improved wear resistance [13]. It can also be used in technical fields to increase corrosive resistance of steel pipes [14]. Overall, the PEO is being actively exploited to introduce functional elements into coatings on biomaterials and beyond biomedical applications [15].…”
Section: Introductionmentioning
confidence: 99%